The effects of core self-evaluations and transformational leadership on organizational commitment - Joo, Baek-Kyoo (Brian); Jun Yoon, Hea; Jeung, Chang-Wook (Leadership & organization development journal, 2012)
Purpose - The purpose of this study is to examine the joint effects of employees' core self-evaluations and perceived transformational leadership of their supervisors on employees' affective commitment to the organization.Design methodology approach - Subjects were drawn from a Fortune Global 500 company in Korea. Descriptive statistics and hierarchical multiple regression analyses were used to explain the variance in organizational commitment.Findings - Core self-evaluations and transformational leadership positively influenced employees' organizational commitment. In terms of effect size, organizational commitment was more related to transformational leadership than core self-evaluations. As for transformational leadership, employees exhibited the highest organizational commitment when their leaders articulated the vision, promoted group goals, and provided intellectual stimulation.Research limitations implications - The sample of this study is likely restricted to a certain group with similar demographic characteristics (e.g. male junior managers with relatively high education levels). This study, like most organizational commitment studies, relied on self-reported and cross-sectional survey method.Practical implications - Since core self-evaluations tend to be stable over time, HR professionals need to recruit and select those with higher core self-evaluations. HR OD professionals can help managers change their leadership in a transformative fashion (vision articulation, group goal promotion, and intellectual stimulation) by providing relevant training programs and developmental relationships such as coaching and mentoring.Originality value - This study took an integrative approach that encompasses personal and contextual factors in a study. It found not only a significant relationship between core self-evaluations and organizational commitment, but also the interaction effects of core self-evaluations and one of the dimensions of transformational leadership.